Responsibility as a Mediator of the Influence of Environmental Identity and Value Orientation on Littering Behavior of Students In Makassar - Basti Tetteng; Ahmad Yasser Mansyur; Nuratthahirah Ansar; Sari Samandatu; Roselina Dwi Hormansyah (Indonesian Journal of Educational Studies, 2025)
behavior, with ecological responsibility acting as a mediating variable. The research was conducted among public senior high school students in Makassar City. Data were collected using a set of valid and reliable Likert-based instruments, including the Environmental-Portrait Value Questionnaire (E-PVQ), the Environmental Identity (EID) Scale, the Responsibility Scale, and the Littering Prevention Behavior Scale. The data were analyzed using Structural Equation Modeling (SEM), and the final model demonstrated a good overall fit. The findings reveal several important relationships. Value orientation was found to have a positive and significant effect on environmental responsibility, indicating that students with strong pro-environmental values tend to feel more responsible for their environment. Environmental identity also positively and significantly influenced environmental responsibility. Furthermore, value orientation showed a positive and significant effect on littering behavior, suggesting that values can directly encourage responsible waste disposal. In contrast, environmental identity did not directly influence littering behavior in a significant way. However, environmental responsibility emerged as a key factor: it positively and significantly predicted littering behavior and served as a mediator in the model. Environmental responsibility successfully mediated the influence of both value orientation and environmental identity on littering behavior.Keywords: value orientation, environmental identity, responsibility, littering behavior, high school students